PERFORMANCE OF COCKEREL CHICKSFED DIETS CONTAINING GRADED LEVELS OF CASHEW (Anarcadium occidentale L.) PULP MEAL - Oyewole, B. O.; Joseph, M.; Ahutu, I. A. (FUDMA JOURNAL OF SCIENCES, 2023)
One hundred and fifty (150) day-old cockerel chicks were used in a five week feeding trial to evaluate five (5) diets, in which cashew pulp meal (CPM) replaced 0%, 10%, 20%, 30% and 40% of maize in T0, T1, T2, T3 and T4, respectively. Each treatment had thirty (30) cockerel chicks, with 10 birds per replicate. All performanceparameters measured were significantly different (P
Keywords: Performance, cockerel, cashew pulp meal